Chinese Adolescents’ Moral Reasoning of Rights Attitudes and Psychological Well-Being - Yang, Shaogang; To, Sharon; Helwig, Charles T. (ETHICS IN PROGRESS, 2017)
This study examined rural and urban Chinese adolescents’ (aged 13–19 years, N = 395) attitudes toward children’s self-determination and nurturance rights, and how these attitudes relate to various dimensions of socialization in their family and school environments, including perceptions of parental and teacher autonomy support and responsiveness and family and school democratic climate. Relations between these variables and psychological well-being also were examined. Perceived parent and teacher autonomy support and responsiveness and democratic climate differentially predicted attitudes toward each type of right and were positively correlated with adolescents’ psychological well-being. Our findings suggest that environments that are structured more democratically and that are responsive to children’s autonomy needs contribute to their psychological health and well-being in diverse cultural settings.